Proliferation rate and cell size analyses of human peripheral blood suspension stem cells from three culturing terms populations - Muniandy, M.K.R.; Ruzanna, A.K.; Intan Zarina, Z.A.; Rohaya, M.A.W.; Sahidan, S.; Majlis, B.Y.; Shahrul Hisham, Z.A. (Penerbit Universiti Kebangsaan Malaysia, 2013)
Stem cells that made up of embryonic stem cells and adult stem cells are well known for their ability to self renew and differentiate into matured cells. Adult stem cells isolated from peripheral blood system were used as the study sample. The objective of this study was to determine the relationship between size and proliferation potential of stem cells from 3 different culturing terms, i.e., short (7 days), medium (14 days), and long (30 days) terms. Density gradient centrifugation was applied in isolating mononucleated cells (MNCs) from peripheral blood sample. Isolated MNCs were washed with Hank’s Balanced Salt Solution and Phosphate Buffer Saline. The MNCs which cultured in complete media were then subjected to proliferation analysis every day for a time period of 30 days. RT-PCR analyses and cell size measurements were carried out at day 7, 14, and 30. Activation of KIT and SLAMF1 marker genes during RT-PCR analyses indicated that the isolated MNCs were stem cells. Analyses of proliferation rate and cell size showed that short term stem cells have the largest cell size with the lowest proliferation potential. While, medium term stem cells gave rise to a smaller stem cell population with higher proliferation potential compared to short term stem cells. Long term stem cells have smallest cell size with highest proliferation potential. In conclusion, each culturing term cell population had their own sizes and can be isolated based on those sizes.